2019
DOI: 10.1007/978-3-030-29736-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Comment Types and Levels of Engagement in Video-Based Learning as a Basis for Adaptive Nudging

Abstract: Video is frequently used as a learning medium in a variety of educational settings, including large online courses as well as informal learning scenarios. To foster learner engagement around instructional videos, our learning scenario facilitates interactive note taking and commenting similar to popular social video-sharing platforms. This approach has recently been enriched by introducing nudging mechanisms, which raises questions about ensuing learning effects. To better understand the nature of these effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The students who contributed the most frequently tended to generate questions rather than building on what others had written. An intervention to encourage students to generate more content [30] simply increased the proportion of shallow and simple (Active mode) messages and did not improve learning gains.…”
Section: The Icap Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…The students who contributed the most frequently tended to generate questions rather than building on what others had written. An intervention to encourage students to generate more content [30] simply increased the proportion of shallow and simple (Active mode) messages and did not improve learning gains.…”
Section: The Icap Frameworkmentioning
confidence: 98%
“…The extended ICAP schema was used to label messages in MOOC discussion forums [31,32]. It was also used to classify student comments on an annotated electronic course text [36] and on MOOC videos [30], although in the latter case the activity was carried out individually with no scope for interaction between participants. Results from these studies indicated that interaction was rare and the majority of messages did not receive contentful responses.…”
Section: The Icap Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the expected content redundancy and the problem of finding the right educational video [29], YouTube is the most recurrent social video tool used in education [26]. In addition, it is one of the first sources for learners when they want to learn something new [5], and it is capable of enhancing the learning experience considering that video is significant to the subject at hand [30]. Four lines of research can be identified in the literature regarding the use of the YouTube platform in education: educational video quality [29,31]; self-directed and long-life learning [21,32]; the cultural dimension [7]; and acceptance and use [15][16][17].…”
Section: Social Video Platforms For Learningmentioning
confidence: 99%
“…This behavior has allowed them, over time, to become platforms to gather information and help to learn [4]. In fact, today, YouTube is the first source for learners when they want to learn something new [5,6].…”
Section: Introductionmentioning
confidence: 99%